A comprehensive evaluation of pectinase, pectinmethylesterase and pectolyase activity - Rajbhar, Karishma; Dawda, Himanshu; Mukundan, Usha (Current Botany, 2021)
Pectin polysaccharide has galacturonic acid with linear chains of α-(1–4)-linked D- galacturonic acid. Rhamnogalacturonan I pectins (RG-I) shows the existence of the repeating disaccharide 4-α-D-galacturonic acid-(1,2)-α-L- rhamnose, which acts as a backbone. Chiefly, D-galactose, L-arabinose, and D-xylose are the sugars types and its proportions of neutral sugars are varied according to the origin of pectin. Pectinase, pectinmethylesterase, and pectolyase enzymes have important applications in food, textile and agricultural industries. These enzymes play an important role in the breakdown of the central part of the plant cell wall. Pectin forms the center part of the plant cell wall. Pectins are termed as structural polysaccharide that has integrity for the steadiness of the plant cell wall. Citrate buffer of molarity 0.1 utilized to verify optimal pH along with temperature, for standardising enzyme activity of pectinase, pectolyase, and pectinmethylesterase by the dinitrosalicylic acid reagent method. Confirmatory check of enzyme’s activity was performed on plant leaves dried particles. Impact of catechin presence in enzyme reaction was too studied. Results delve into degradation of the plant polysaccharide by applying these enzymes. An increase in the monosaccharide galacturonic acid quantity was also significant. The highest release of the polyphenols was found due to pectolyase followed by pectinmethylesterase and pectinase. Pectinmethylesterase effect showed the maximum release of the flavonoids followed by pectinase and pectolyase which was remarkable.